EFEKTIVITAS GURU PAI DALAM PEMBELAJARAN MENGGUNAKAN MODEL KOMUNIKASI DI SMPS IT IBU HARAPAN BENGKALIS - Kholijah, Siti; Sofiani, Ika Kurnia (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research is motivated by several symptomps of the problem that researchers have identified, namely first, form the internal side, many teachers still do not master effective communication models. Second, and external system, namely the limited time available in learning and differences in the backgrounds of students so that the learning styles that arise are also different. This research is defferent and this research is to find out how much the teacher’s effective communication model relates to improving student learning outcomes in Class VII PAI learning at SMP IT Ibu Harapan Bengkalis. Theory used in this research is an effective communication model and learning outcomes. The type of this research is quantitative research with data collection techniques in the form of observation, questionnaires, and documentation. The result of this research are that there is a relationship between the teacher’s effective communication model in improving student learning outcomes in class VII PAI learning at SMP ITIbu Harapan Bengkalis wich show the result are at a value of 0,508 for a value of 0,508 lies between 0,400-0,599 wich means it has a moderate or sufficient correlation